Conditions favorisant les apprentissages des élèves sourds lors de Lecture Interactive d’un album dans une classe bilingue - Edyta Tominska (Recherches en Éducation)
This article’s objective is to show the progress of young deaf learners in literacy knowledge construction in an Interactive Reading situation proposed in a bilingual specialized class for deaf children. Our analysis of the didactic interactions shows the joint construction of a Zone of Common Meaning (ZCM) inside which we observe shared understandings about the storybook components negotiated and constructed by the different partners. The interactional analysis in a classroom situation focuses on conditions that promote learning of deaf pupils. These conditions are connected to the complex didactic situation implying several literacy knowledge components, but also in the use of two languages, that allow a wide linguistic development. This bilingual situation points out the resources, needed for the observed children to understand their partners and to be understood.